2022
DOI: 10.1002/adfm.202208565
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Vacancy‐Rich Sr2MgSi2O7:Eu2+,Dy3+ Long Afterglow Phosphor as a Round‐the‐Clock Catalyst for Selective Reduction of CO2 to CO

Abstract: Solar‐driven CO2 conversion to fuels is a central technique for closing the anthropogenic carbon cycle, but to date is limited by the intermittent solar flux. To face this challenge, a catalyst is needed that can work well in both light and dark. Here, surface oxygen vacancies are created in a Sr2MgSi2O7:Eu2+,Dy3+ long‐afterglow phosphor with long‐time and high charge storage capacity (denoted as Vo‐SMSED) as both electron transfer station and active sites for molecule activation. The strong ability for oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…For instance, Lotsch et al demonstrated that highly reductive radicals with lifetimes longer than the diurnal cycle can be formed on a cyanamide-functionalized carbon nitride polymeric network under irradiation (Figure 5g). [48] Then, the trapped electrons were released for hydrogen production in the dark, thus [40] e) Ti-MIL-125-NH 2 with the formation of reductive Ti 3 + intermediate induced by the ligand-to-metal charge transfer (LMCT), [46] f) metal oxides with oxygen vacancies as the electron trapping sites, [47] Copyright 2022, Wiley-VCH GmbH, Weinheim, g) functionalized C x N y , [48] h) MOF confined Ru-bpy hybrids, [50] i) Cu-based metal complex that can store and release two electrons, [51] and j) POMs/Ru-bpy molecular dyad integrating the properties of photosensitizers and photocatalysts. [52] Copyright 2022, Nature Publishing Group.…”
Section: Decoupled Photochemical (D-pc) Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Lotsch et al demonstrated that highly reductive radicals with lifetimes longer than the diurnal cycle can be formed on a cyanamide-functionalized carbon nitride polymeric network under irradiation (Figure 5g). [48] Then, the trapped electrons were released for hydrogen production in the dark, thus [40] e) Ti-MIL-125-NH 2 with the formation of reductive Ti 3 + intermediate induced by the ligand-to-metal charge transfer (LMCT), [46] f) metal oxides with oxygen vacancies as the electron trapping sites, [47] Copyright 2022, Wiley-VCH GmbH, Weinheim, g) functionalized C x N y , [48] h) MOF confined Ru-bpy hybrids, [50] i) Cu-based metal complex that can store and release two electrons, [51] and j) POMs/Ru-bpy molecular dyad integrating the properties of photosensitizers and photocatalysts. [52] Copyright 2022, Nature Publishing Group.…”
Section: Decoupled Photochemical (D-pc) Catalysismentioning
confidence: 99%
“…d)-j) Typical decoupled photocatalytic systems that undergo light harvesting and charge transfer and separation processes under irradiation and produce chemicals or fuels in the dark. d) Conjugated organic polymer films (COPFs) bearing tautomer motifs and performing overall CO 2 splitting,[40] e) Ti-MIL-125-NH 2 with the formation of reductive Ti 3 + intermediate induced by the ligand-to-metal charge transfer (LMCT),[46] f) metal oxides with oxygen vacancies as the electron trapping sites,[47] Copyright 2022, Wiley-VCH GmbH, Weinheim, g) functionalized C x N y ,[48] h) MOF confined Ru-bpy hybrids,[50] i) Cu-based metal complex that can store and release two electrons,[51] and j) POMs/Ru-bpy molecular dyad integrating the properties of photosensitizers and photocatalysts [52]. Copyright 2022, Nature Publishing Group.…”
mentioning
confidence: 99%
“…Thus, the abundant CO 2 feedstock has driven researchers to achieve CO 2 chemical utilization. 67 Accordingly, CO 2 conversion using sunlight-driven photocatalysts is a crucial technique for closing the carbon cycle; however, intermittent solar flux is the bottleneck of catalysis. Thus, to address this, Pei et al successfully synthesized oxygen-deficient Vo-SMSED, possessing electron transfer paths and active sites.…”
Section: Applicationmentioning
confidence: 99%
“…[2][3][4][5][6] Furthermore, the photocatalysis method has been considered as a feasible means for harvesting light energy in chemical bonds through different photoexcited reactions, like organic pollutant oxidation, CO 2 reduction, H 2 O splitting, H 2 O 2 preparation and valued organics synthesis. [7][8][9][10][11][12][13][14][15] Over recent decades, a considerable number of semiconductors such as metal oxides, metal sulfides, and nitride materials have been exploited as photocatalysts for various photocatalytic reactions. [16][17][18][19][20] Among them, graphitic carbon nitride (g-C 3 N 4 ) possessing outstanding light-response ability has shown great promise because of its facile synthesis, tunable band gap structure, good chemical stability, and environmentally friendly properties.…”
Section: Introductionmentioning
confidence: 99%